Effects of model-based teaching on pre-service physics teachers' conceptions of the moon, moon phases, and other lunar phenomena - BEKİROĞLU, FERAL (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2007)
The purpose of this study was twofold. First, it was aimed to identify Turkish pre-service physics teachers' knowledge and understanding of the Moon, Moon phases, and other lunar phenomena. Second, the effects of model-based teaching on pre-service teachers' conceptions were examined. Conceptions were proposed as mental models in this study. Four different questionnaires including 22 generative, explanation, and factual questions were used through the study. The pre-service physics teachers' mental models generated in response to lunar phenomena might be representations of their naive knowledge as a result of their causal observations and experiences with the world, and their misconceptions as a result of inconsistencies between their naive knowledge and scientific knowledge. Therefore, the pre-service teachers' mental models were categorized based on the work by Chi and Roscoe. Some of the pre-service teachers' mental models shifted from flawed or incomplete mental models to correct mental models of the Moon and lunar phenomena with the facilitation of model-based teaching. The conclusions of the study carry implications for curriculum developers and teacher education.
Keywords: lunar phenomena; model-based teaching; moon phases; pre-service physics teachers; STUDENTS; KNOWLEDGE; EARTH; AGE